ANALISIS TEKNO EKONOMI PEMANFAATAN SAMPAH PASAR SEBAGAI BAHAN PEMBUATAN PUPUK ORGANIK CAIR - Dewi Diniaty; Jaka Prindra illahi; Wresni Anggraini; Ekie Gilang Permata; Silvia Silvia (Universitas Ahmad Dahlan Indonesia, 2020)
The Selasa Panam Market is a traditional market where there are many piles of garbage around the market area. This pile of garbage can cause environmental pollution which causes unpleasant odors. This study aims to manufacture liquid organic fertilizer made from market waste by adding EM4, Yeast, and Whey Kefir, testing the nutrient content of N, P, K in liquid organic fertilizer, analyzing the economic techno of liquid organic fertilizer based on HPP and BEP. This research using a completely randomized design method is used to determine the treatment of making liquid organic fertilizer and variable costs to calculate the cost of production (HPP). Then the BEP method to determine when the break-even point will be reached. Success has been made in the manufacture of liquid organic fertilizers made from market waste giving EM4, Yeast, and Whey Kefir bacteria. N, P, K nutrient content test results obtained sample C has the best results with N values of 0.4129%, P 0.1223%, and K 0.2101%. HPP on organic fertilizer obtained was Rp. 5,222 / liter and BEP obtained as much as 321 liters for a year so that the BEP can be reached within 71 days. With this research can be found knowledge about the use of market waste as an ingredient for making liquid fertilizer and making products that can be used by others.